THE SKILLS FOR EFFECTIVE DECISION MAKING OF PUBLIC ADMINISTRATORS - Etleva LESKAJ (Business Excellence and Management, 2015)
In this article will be treated different skills for public administrators, during the process of decision making, which affect the effectiveness of their decisions, and thus will also affect the fulfillment of the objectives of the organizations they lead. The main purpose of the article is to identify the skills that demonstrate public administrators during decision making in order to define how good are their decison making process. On the basis of secondary and primary research, the authors would discuss the findings in order to identify the problems faced during these processes of decision-making public administrators.